Analysis and evaluation of university intellectual capital of peru public - Yenque Dedios, Julio Antolín (2016)
The growth of intellectual capital, is an important item in a university institution. The failure of this heading must face through strategic actions. Facilitate the creation of new knowledge, underpins innovation through reuse and support of the people through organizations ability to achieve a better performance in the company.Human capital is the source of innovation and renewal of universities, and is located in: great ideas that appear in the laboratory, the knowledge generated through the research process, the experiences obtained in the work performance, or the skills acquired by staff through a process of organizational development. It is imperative to manage knowledge through a different conception regarding human capital, which, as one of the axes of intellectual capital, become actors facilitators of management and strategic partners of the operation to be increasingly more efficient and effective through the rationality of resources that are increasingly scarce.